Endothelin receptor antagonists target EDNRB and modulate the progression of idiopathic pulmonary fibrosis via anoikis-related genes - Ning, Pengfei; Zhao, Huiru; Weng, Yujie; Guo, Yanhua; Jia, Rong (Frontiers in Medicine, 2025)
Idiopathic pulmonary fibrosis (IPF) progression involves dysregulation of anoikis-related mechanisms, though the precise molecular drivers remain unclear. Through integrated analysis of IPF and normal lung tissue datasets, we identified 19 anoikis-related genes (ARGs) with EDNRB, MMP7, and CXCL12 showing significant differential expression (p < 0.05). Functional characterization revealed these ARGs predominantly regulate cell chemotaxis and inflammatory pathways, with protein network analysis identifying CXCL12 and CCL5 as central regulators. Clinically relevant findings demonstrated that EDNRB downregulation correlates with fibrotic progression, while ROC analysis validated multiple ARGs as diagnostic biomarkers (AUC > 0.8). Crucially, we discovered that FDA-approved endothelin receptor antagonists (bosentan/sitaxentan) attenuate fibrosis through EDNRB upregulation, positioning these repurposable drugs as novel therapeutic candidates. These findings establish EDNRB-mediated anoikis regulation as a key mechanism in IPF and urgently warrant clinical trials to validate endothelin receptor antagonists for targeted anti-fibrotic therapy.